2017
DOI: 10.1097/mot.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in allograft vasculopathy

Abstract: Purpose of review Despite considerable advances in controlling acute rejection, the longevity of cardiac and renal allografts remains significantly limited by chronic rejection in the form of allograft vasculopathy (AV). This review discusses recently reported mechanistic insights of AV pathogenesis as well recent clinical evaluations of new therapeutic approaches. Recent findings Although adaptive immunity is the major driver of AV, natural killer cells mediate vasculopathic changes in a transplanted mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 70 publications
0
39
0
Order By: Relevance
“…Currently, there are many methods used for promoting fracture healing in clinics [1,2,[10][11][12]. Surgical intervention and autologous bone transplantation are the gold standard of current treatment in the event of fracture nonunion, but the trauma is so large that some patients may need multiple surgeries for years [13][14][15]. Autologous bone is generally taken from the iliac crest or fibula of the patient, which is more damaging to the patient and is prone to infection after sur-gery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are many methods used for promoting fracture healing in clinics [1,2,[10][11][12]. Surgical intervention and autologous bone transplantation are the gold standard of current treatment in the event of fracture nonunion, but the trauma is so large that some patients may need multiple surgeries for years [13][14][15]. Autologous bone is generally taken from the iliac crest or fibula of the patient, which is more damaging to the patient and is prone to infection after sur-gery.…”
Section: Introductionmentioning
confidence: 99%
“…The cell components in allogeneic bones are mostly dead and do not have their own osteogenic ability. Studies have found that allogeneic bone treatment for nonunion fractures takes about 12 months for allogeneic bone surface union; indeed, internal osteogenesis is very slow, occurring at a rate of only 15-20% within five years, and deep repair hardly occurs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The major characteristics of chronic allograft rejection are fibrosis and allograft vasculopathy. [31][32][33]83 Although the mouse model cannot replicate all features of chronic allograft rejection in humans, in cardiac allografts harvested at 28 days following transplantation, we observed significantly less fibrosis, lower expression of VCAM and P-selectin, and lesser degrees of intimal thickening in the MMF-NP-treated recipients. To more directly examine the effect of MMF-NP on endothelial cell activation, we also returned to the in vitro model of TNFα stimulated HUVEC, incubated either with PBS, free MMF, or MMF-NP, and we found a significant reduction in the expression of adhesion molecules after incubation with MMF-NP, similar to our results in the heart allograft.…”
Section: Acs Nanomentioning
confidence: 81%
“…Although the role of CD8 + Tem cells in AV pathogenesis is unclear, NK cells have been implicated as mediators of graft damage in allograft vasculopathy by engaging donor-specific antibodies bound to graft ECs. NK cells are effectors of antibodydependent cytotoxicity (ADCC), which can be enhanced by IL-15 (33,34). IL-15 transpresentation by ECs to NK cells may promote allograft vasculopathy pathogenesis by enhancing NK cell activation and cytolytic activity.…”
Section: Discussionmentioning
confidence: 99%